Art and Mindfulness as Elements of Socioemotional Education in the Classroom - Reza-Flores, Ricardo Alberto (2026)
Introduction. Emerging value frameworks within educational settings seek to develop disruptive pedagogical practices that promote socioemotional well-being, including the integration of art and mindfulness. Objective. This study aimed to examine the subjectivities of primary school teachers in Mexico City, Mexico, and Neiva, Colombia, to determine whether these actors recognize and incorporate mindfulness techniques and art as transformative elements of socio-emotional education. Methodology. A cross-sectional quantitative design was employed. Data were collected using an ad hoc instrument comprising three analytical dimensions: performance and achievement, emotions, and professional development. The instrument demonstrated strong reliability (Cronbach’s alpha of 0,88). The dimensions were analyzed using Pearson’s chi-square and Wilcoxon rank-sum tests. Results. Statistically significant differences were identified in how teachers from both countries perceive their students’ learning, grades, achievements, attitudes, and cognitive skill development they consolidate. Furthermore, when art and mindfulness are incorporated into classroom experiences, predominantly positive emotions are reported. Conclusions. Socio-emotional education repositions and redefines quality, relevance, equality, and well-being of individuals, which can be achieved through teachers committed to ongoing professional development  to integrate art and mindfulness into daily school life.